Effect of Fermentation on the Bioactive Compounds of the Black Soybean and Their Anti-Alzheimer’s Activity - Shabbir, Umair; Tyagi, Akanksha; Ham, Hun Ju; Elahi, Fazle; Oh, Deog-Hwan (Frontiers in Nutrition, 2022)
Black soybean is one of the nutritious crops and is being used in traditional medicines in Asian countries. In the present study, we fermented black soybean and screened against in vitroin vitro Alzheimer's disease (AD) biomarkers such as cholinesterase enzymes, inflammatory factors, oxidative stress, and presence of γ-aminobutyric acid (GABA) levels. Firstly, we fermented black soybean with different lactic acid bacteria (LABs) and selected the Pediococcus acidilactici as the best LAB on the basis of GABA levels in the fermentate. We have found that black soybean fermented with Pediococcus acidilactici significantly inhibited the inflammatory factors (proteinase, protein denaturation, and lipoxygenase) and cholinesterase enzymes than non-fermented samples. An increase in the antioxidant capacity (FRAP, ABTS, and DPPH), anthocyanins, phenolics, flavonoids, and GABA content was also observed in fermented samples. Moreover, UHPLC-ESI-QTOF-MS/MS technique identified 38 bioactive components, including polyphenols, amino acids, and fatty acids. Among identified components, 8 polyphenols bioactive compounds were quantified, and an increase in the concentration of daidzein, genistein, glycitein, (+)-catechin, quercetin, and gallic acid was observed in fermented samples. However, the concentration of rutin and soyasaponin was higher in raw samples. These results indicated that fermentation of black soybean with Pediococcus acidilactici is a promising approach that can be used to develop functional foods to inhibit/prevent AD and other neurodegenerative diseases